Post Covid-19 Pandemic: Evaluating The Effectiveness Of Digital Learning Platforms For Students' Engagement In Mathematics Lessons - Morenikeji Alex AKANMU; Toheeb Olalekan IDRIS; Comfort Olawumi ADENIYI (STKIP Rokania Pasir Pangaraian, 2023)
School closures in Nigeria during the Covid-19 pandemic left millions of students and lecturers dependent on online teaching and learning. Online teaching and learning are an unprecedented experience for most lecturers and students; consequently, there was then a limited experience with it. This study examined and evaluated the integration of Digital Learning Platforms into the teaching and learning of mathematics during the COVID-19 pandemic. Furthermore, it assesses the perception of both students and lecturers about the use of Digital Learning Platforms and their general rating of the effectiveness of the available digital platforms for mathematics teaching and learning processes. Simple random sampling procedure was used to select twenty (20) lecturers and hundred (100) undergraduate students from a federal government owned university in the Southwestern State of Nigeria. The percentage was used to analyze the respondents’ demographic information while the Chi-Square was adopted to analyze the data. Results of the analysis of the formulated hypothesis indicated that two or more digital platforms were used by the lecturers to teach mathematics in post covid-19 pandemic and both Zoom and Google Meet are considered effective for mathematics teaching in post covid-19 pandemic. Also, lecturer’s digital skills are dependent of the integration of digital learning platforms in mathematics teaching and student’s academic engagement exposure is independent of digital learning in pre-and-post-covid era Based on the findings of the study, it was suggested that digital technologies may be included in mathematics curricula at various stages of education and education stakeholders should take advantage of the findings of this study to encourage lecturers to continue using technologies in mathematics teaching.